The School of Reading Nikolai Gumilev: Seven Students (I. Pribludnyi, D. Kedrin, O. Mochalova, B. Pasternak, O. Mandelstam, M. Tsvetaeva, A. Akhmatova) - Тименчик, Роман (Literatūra, 2022)
Elaborating literary scholar Boris Tomashevsky’s actionable metaphor “schools” of readers, this historical study picks up seven ‘graduates’ from the depth of poet Nikolai Gumilev’s followers.